Peran Media Sosial sebagai Medium untuk Memaksimalkan Keterbukaan Informasi Publik di KPU Kabupaten Jombang - Umma, Wafa Patria; Ahmad, Nyarwi (Jurnal Komunikasi Nusantara, 2025)
Previous studies have largely focused on the normative implementation of the Public Information Disclosure Act (UU KIP) or the role of the Information and Documentation Management Officer (PPID), without thoroughly examining public communication strategies through social media. The STOC culture-based approach (Sharing, Transparency, Openness, Collaboration) by Khan (2017) has rarely been applied in the analysis of information disclosure practices. This research addresses that gap by evaluating the communication strategy of the General Elections Commission (KPU) of Jombang Regency in utilizing social media as a means of ensuring public information transparency in a more interactive and participatory manner. This study adopts a qualitative approach with descriptive analysis and a case study design. The findings indicate that the elements of Sharing, Transparency, and Openness have been well implemented, whereas Collaboration remains underutilized. Regarding the phases of public information disclosure through social media use by KPU Jombang: in the information dissemination phase, KPU actively shares content; in the mass collaboration phase, public participation is still limited to responses and comments on KPU’s social media, not yet at the core of public services; and in the social transaction phase, implementation remains minimal. This limitation is attributed to KPU's hierarchical structure, which adheres to centralized regulations. Nevertheless, KPU Jombang successfully received recognition as an Informative Public Agency in 2024. This study recommends strengthening the legal framework, increasing the digitalization budget, and encouraging further research on similar practices in other public institutions. Abstrak Penelitian sebelumnya lebih banyak berfokus pada implementasi normatif UU KIP atau peran PPID, belum mengkaji secara mendalam strategi komunikasi publik melalui media sosial. Pendekatan berbasis budaya STOC (Sharing, Transparency, Openness, Collaboration) oleh Khan (2017) belum banyak digunakan dalam analisis keterbukaan informasi. Penelitian ini mengisi kekosongan dengan mengevaluasi strategi komunikasi KPU Kabupaten Jombang dalam pemanfaatan media sosial sebagai sarana transparansi informasi publik secara lebih interaktif dan partisipatif. Pendekatan penelitian ini adalah kualitatif dengan analisis deskriptif, dan jenis penelitian studi kasus. Hasil penelitian menunjukkan bahwa budaya Sharing, Transparency, dan Openness telah diterapkan secara baik, namun budaya Collaboration masih belum maksimal. Terkait fase (tingkat) keterbukaan informasi publik melalui penggunaan media sosial oleh KPU Kabupaten Jombang dihasilkan bahwa; Pada fase sosialisasi informasi, KPU aktif membagikan konten. Pada fase kolaborasi massal, partisipasi publik masih sebatas melalui respons dan komentar di media sosial KPU, belum inti pelayanan. Dan pada fase transaksi sosial, penerapannya masih terbatas. Hal ini disebabkan oleh struktur hierarkis KPU yang mengikuti regulasi dari tingkat pusat. Kendati demikian, KPU Kabupaten Jombang berhasil meraih penghargaan sebagai Badan Publik Informatif pada tahun 2024. Penelitian ini merekomendasikan pentingnya penguatan dasar hukum, peningkatan anggaran digitalisasi, serta pengembangan riset serupa pada lembaga publik.